Análise de comparação entre elitismos na calibração de fatores de atrito em redes hidráulicas por meio do método transiente inverso com aplicação de algoritmo genético - Silva, Francisco Ícaro Lopes da (2017)
For some time, due to its complexity, the calibration of parameters in transient hydraulic networks was neglected. However, studies related to this phenomenon, especially with respect to the friction factor have been growing in recent times. Simulations of the equilibrium conditions of a hydraulic distribution network become one of the most important steps in the technical analysis of water supply systems. In order to identify and estimate the parameters of a hydraulic network, from observed data of transient loads, a computational model was developed. In general, the physical parameters of the network such as friction factors, absolute roughness, diameters and the identification, measurement and quantification of leaks are unknown quantities. This work aims at the identification and calibration of the friction factors by means of a combination of the Inverse Transient Method - MTI - with the Genetic Algorithm - AG. Next to this combination was used the Method of Characteristics - MOC - to solve the equations of the flow in permanent and transient regime in networks of pipes. The hypothetical hydraulic net under analysis consists of eight variable demand nodes, ten tubes and a quota reservoir equivalent to 60m, being submitted to a 30s transient. The analyzes were performed through programs that apply the technique of optimization of the genetic algorithm to find the optimal values ​​of the hydraulic load in the observed node. A comparative study will be carried out between two types of elitism in order to evaluate the effects produced in the identification and calibration of the friction factors in transient conditions. The steady state conditions are known. Five elitism rates were applied to each initial population in order to analyze the influence on the calibration result. Elitism 2 presented smaller errors than elitism 1, both for the average processing and for better processing, even with higher objective functions. The rate of best efficiency for the application of elitism 1 and 2 was 70%. The hydraulic transient is directly related to the definition of the parameters of the genetic algorithm.